Candid science II : conversations with famous biomedical scientists - Hargittai, István (Candid science, 2002)
This invaluable book contains 36 interviews, including 26 with Nobel laureates. It presents a cross-section of biomedical science, a field that has been dominant in science for the past half century. The in-depth conversations cover important research areas and discoveries, as well as the roads to these discoveries, including aspects of the scientists' work that never saw publication. They also bring out the humanness of the famous scientists - the reader learns about their backgrounds, aspirations, failings, and triumphs. The book is illustrated with snapshots of the conversations and photos provided by the interviewees. It is a follow-up to the critically acclaimed Candid Science: Conversations with Famous Chemists, by the same author.